EXPLORATION NON-SYMBIOTIC NITROGEN FIXING BACTERIA PRODUCED IAA (INDOLE ACETIC ACID) AND PHOSPHATE SOLUBILIZATION FROM APPLE’S TREE RHIZOSPHERE IN BATU, EAST JAVA - Ratna Fadhilah Israwan; Tri Ardyati; Suharjono Suharjono (Biotropika: Journal of Tropical Biology, 2015)
Biofertilizer is fertilizer contain microbes that help provide available nutriens for plants. Non symbiotic nitrogen fixing bacteria has been widely utilized as a biofertilizer agent. The objective of this research was to explore bacteria have ability in fixing nitrogen, producing IAA (indole acetic acid) and solubilizing phosphate from rhizosfer of Apple tree in Batu City. East Java. Isolation of soil sample from Apple tree rhizosphere was carried out using serial dilution. Nitrogen fixation ability was assayed qualitatively using nitrogen free bromothymol blue (Nfb) medium enriched with tryptophan. Quantitative measurement of Nitrogen fixation was done by Visocolor ammonium alpha detection kit. IAA production was observed in Luria Bertani medium enriched with tryptophan and Salkowski reagent. Detection of phosphate solubilization was done using Pikovskaya agar and Mo-blue reagent. Four isolates were obtained, isolates TR1, TR2, TR4 and TR5. All isolates have ability to fix nitrogen and to produce IAA. Isolate TR5 has the highest ability of nitrogen fixing (1 mg/L). Isolate TR1 produce maximum IAA concentration (793,55 µg/mL) at 48 hours. Isolate TR4 has the highest ability to solubilize phosphate (31,28 ppm) with index of phosphate solubization 1,21. Isolate TR1, TR4 and TR5 are potential as biofertilizer agents. Keywords: Biofertilizer, IAA, nitrogen fixation, phosphate, rhizosphere